5(x-6)-6x(x-5)=x+5-(x-4)

Simple and best practice solution for 5(x-6)-6x(x-5)=x+5-(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-6)-6x(x-5)=x+5-(x-4) equation:


Simplifying
5(x + -6) + -6x(x + -5) = x + 5 + -1(x + -4)

Reorder the terms:
5(-6 + x) + -6x(x + -5) = x + 5 + -1(x + -4)
(-6 * 5 + x * 5) + -6x(x + -5) = x + 5 + -1(x + -4)
(-30 + 5x) + -6x(x + -5) = x + 5 + -1(x + -4)

Reorder the terms:
-30 + 5x + -6x(-5 + x) = x + 5 + -1(x + -4)
-30 + 5x + (-5 * -6x + x * -6x) = x + 5 + -1(x + -4)
-30 + 5x + (30x + -6x2) = x + 5 + -1(x + -4)

Combine like terms: 5x + 30x = 35x
-30 + 35x + -6x2 = x + 5 + -1(x + -4)

Reorder the terms:
-30 + 35x + -6x2 = x + 5 + -1(-4 + x)
-30 + 35x + -6x2 = x + 5 + (-4 * -1 + x * -1)
-30 + 35x + -6x2 = x + 5 + (4 + -1x)

Reorder the terms:
-30 + 35x + -6x2 = 5 + 4 + x + -1x

Combine like terms: 5 + 4 = 9
-30 + 35x + -6x2 = 9 + x + -1x

Combine like terms: x + -1x = 0
-30 + 35x + -6x2 = 9 + 0
-30 + 35x + -6x2 = 9

Solving
-30 + 35x + -6x2 = 9

Solving for variable 'x'.

Reorder the terms:
-30 + -9 + 35x + -6x2 = 9 + -9

Combine like terms: -30 + -9 = -39
-39 + 35x + -6x2 = 9 + -9

Combine like terms: 9 + -9 = 0
-39 + 35x + -6x2 = 0

Factor a trinomial.
(-13 + 3x)(3 + -2x) = 0

Subproblem 1

Set the factor '(-13 + 3x)' equal to zero and attempt to solve: Simplifying -13 + 3x = 0 Solving -13 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 3x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + 3x = 0 + 13 3x = 0 + 13 Combine like terms: 0 + 13 = 13 3x = 13 Divide each side by '3'. x = 4.333333333 Simplifying x = 4.333333333

Subproblem 2

Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5

Solution

x = {4.333333333, 1.5}

See similar equations:

| 1900+5x=2 | | 17x-5=14x-8 | | 7/22x11/35 | | y=2x+5cos^3x | | -3(x+4)=2(x-5) | | 0=x^4-3x^3-8x^2+12x+16 | | 3x-2=-2x-8 | | 30x=6x | | -5(4x+1)-5=-3(x+4)+2x | | 15-6n+2=4n-1 | | y=xsquared+1 | | 11x+13=55 | | -10z=2.7 | | 4-3m=-4m+5 | | 15x=11000 | | 10-6=4 | | 10z=2.7 | | Y=(x-2)squared | | 41790=5+210t | | 8g-4=5(2g+1) | | 4x+7=2x+47 | | 3/2*7/3 | | 65=5+2.5x | | 36+b^2=324 | | (2/9x)-(1/7)=(1/6) | | 6x+4x-4=26 | | 5(4x+5)=-13+18 | | 11x+13=58 | | 3x+25-9=0 | | (4/5x)=-12 | | 2m+4m-3m=24 | | x^9=20 |

Equations solver categories